Hot target magnetron sputtering enhanced by RF-ICP source: Microstructure and functional properties of CrNx coatings. (June 2022) - Grudinin, V.A.; Bleykher, G.A.; Krivobokov, V.P.; Semyonov, O.V.; Obrosov, A.; Weiβ, S.; Sidelev, D.V.
Abstract: CrNx coatings were deposited at high rates (100–130 nm/min) using hot Cr target magnetron sputtering enhanced by a radio-frequency inductively coupled plasma (RF-ICP) source in an Ar + N2 atmosphere. Besides separation of inert and reactive atmosphere, the RF-ICP source can be an effective tool for ion assistance in case of coating growth and to tailor film parameters. The effects of nitrogen flow rate and substrate bias potential on microstructure and functional properties of the CrNx coatings were investigated. An increase in nitrogen flow rate favored the formation of a looser microstructure of the coatings, while substrate biasing had the opposite effect. The functional properties were strongly dependent on the phase composition of the CrNx coatings. The change in coating microstructure significantly affected hardness, elastic modulus, adhesion, friction coefficients and corrosion resistance. The results indicated that ion assistance can be a key feature for regulating functional properties in the considered type of coating deposition. Cr2 N and CrN compound coatings with high hardness (∼20 GPa) and low corrosion current density ( i corr ∼ 3–5·10 −9 A/cm 2 ) in a 3.5 wt% NaCl solution were obtained by high-rate deposition. Highlights: Functional properties of CrNx coatings prepared by high-rate deposition. Change of coating microstructure due to increasing N2 flow rate. Influence of ion bombardment on properties of CrN coatings.